2020
DOI: 10.21203/rs.3.rs-48864/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Left hemispheric deficit in the sustained neuromagnetic response to periodic click trains in children with ASD.

Abstract: Background: Deficits in perception and production of vocal pitch are often observed in people with autism spectrum disorder (ASD), but the neural basis of these abnormalities is unknown. In magnetoencephalogram (MEG), spectrally complex periodic sounds trigger two continuous neural responses – the auditory steady state response (ASSR) and the sustained field (SF). It has been shown that the SF in neurotypical individuals is associated with low-level analysis of pitch in the ‘pitch processing center’ of the He… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…In accordance with the previous findings (Edgar et al, 2016; Maurizi et al, 1990; Poulsen et al, 2009; Stapells et al, 1988; Stroganova et al, 2020), we showed a relationship between the strength of 40 Hz ASSR and children's age. Specifically, the results revealed the age‐related increase of 40 Hz ITPC in the right hemisphere in our sample of 7‐to‐12‐year‐old children, and this corresponds to studies which showed a monotonic enhancement of both power and ITPC of auditory gamma oscillations from childhood to the early adolescence (Edgar et al, 2016; Poulsen et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In accordance with the previous findings (Edgar et al, 2016; Maurizi et al, 1990; Poulsen et al, 2009; Stapells et al, 1988; Stroganova et al, 2020), we showed a relationship between the strength of 40 Hz ASSR and children's age. Specifically, the results revealed the age‐related increase of 40 Hz ITPC in the right hemisphere in our sample of 7‐to‐12‐year‐old children, and this corresponds to studies which showed a monotonic enhancement of both power and ITPC of auditory gamma oscillations from childhood to the early adolescence (Edgar et al, 2016; Poulsen et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…The analysis of phase consistency across the trials (or ITPC)—a robust measure of the neural response to periodic auditory signal (Tan et al, 2015)—revealed a right hemispheric dominance of 40 Hz ASSR, indicating that the ITPC‐value was higher in the right auditory ROI. This is in line with the previous studies in both children (Edgar et al, 2016; Poulsen et al, 2009; Stroganova et al, 2020) and adults (Pellegrino et al, 2019; Ross et al, 2005). Some authors hypothesized that this asymmetry can be explained by the fact that the right auditory cortex is specialized for processing the temporal periodicity of the sound (Ross et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations